Komparasi Metode Simple Additive Weighting dan Profile Matching dalam Penentuan Pemberian Beasiswa di SMA Negeri 1 Abiansemal - Christina Purnama Yanti; Pande Putu Sukma Awantari; I Gede Iwan Sudipa; Ni Luh Wiwik Sri Rahayu Ginantra (JURIKOM (Jurnal Riset Komputer), 2021)
SMA Negeri 1 Abiansemal is an educational institution with a state status located on Jalan Majapahit, Blahkiuh Village, Abiansemal District, Badung Regency which accommodates approximately 1,300 students. This school has a scholarship program for underprivileged and high achieving students. In this case study, four criteria are used, including information about being unable, parents' income, number of dependents, and average report cards. In this study, the authors conducted a comparative analysis of two methods, namely the SAW method (Simple Additive Weighting) and Profile Matching to find out which method was most suitable for use in determining the award of scholarships at SMA Negeri 1 Abiansemal by looking at the results of the comparison on the sensitivity test, then the method that has higher sensitivity values will be used in future system implementations so that the results obtained are more accurate. From the sensitivity test that has been carried out, the results obtained that the percentage sensitivity of the SAW method is 5.9166% or rounded to 6% while the Profile Matching method is 27% which can be concluded that the suitable method in this case is the Profile Matching method because this method has higher sensitivity than the SAW (Simple Additive Weighting) method.